Postharvest Dynamics of Photosynthesis in Fresh‐Cut Lettuce - Steensma, Priscille; Shapiguzov, Alexey; Annala, Leevi; Vainonen, Julia P.; Mikkonen, Kirsi S.; Kangasjärvi, Saijaliisa (Wiley-Blackwell, 2025)
Increasing the availability of fresh vegetables and reducing food waste are essential for healthy and sustainable production. However, fresh-cut vegetables such as lettuce (Lactuca sativa L.) often experience rapid quality loss after harvest and processing. To maintain freshness in retail, modified atmosphere packaging (MAP) with low oxygen (O2) and high carbon dioxide (CO2) concentrations, combined with refrigeration, is commonly used. Packaged leaves are then displayed under dark or low-light conditions. The postharvest physiology of lettuce under these conditions (including changes in energy metabolism, photosynthesis, senescence progression, and light-dependent metabolic alterations) remains poorly understood, limiting the development of strategies to extend shelf life. Using spectroscopic and biochemical approaches, we investigated the physiological changes in fresh-cut lettuce stored in MAP under refrigeration in either darkness or constant low light. Our analysis revealed distinct light-dependent and light-independent adjustments in photosynthesis. MAP triggered rapid and dramatic changes in photosynthetic light reactions, detectable within 1 h of packaging, as observed by pulse amplitude modulated (PAM) and OJIP kinetics assays. These changes were likely associated with compromised electron sink strength in the photosynthetic electron transfer chain and altered dynamics of the energy component of nonphotochemical quenching (qE-NPQ). Notably, these functional alterations coincided with only minor modifications in photosynthetic supercomplexes, as determined by blue native gel electrophoresis. The MAP-induced changes in photosynthesis deteriorated during storage in darkness but were reversed by storage under low light, likely due to photosynthetic gas exchange. Our findings provide new insights into photosynthesis of packaged lettuce and highlight promising physiological readouts for assessing lettuce quality in retail settings.
Keywords: chlorophyll fluorescence; lettuce; modified atmosphere packaging; NPQ; regulations of photosynthesis